Effect of stem sizing and position on short‐term complications with canine press fit cementless total hip arthroplasty. Issue 6 (29th April 2017) - Townsend, Sarah; Kim, Stanley E.; Pozzi, Antonio
Abstract: Objective: To determine the influence of stem sizing and positioning with early subsidence and stem complications with cementless (BFX) total hip arthroplasty (THA). Study design: Retrospective case series. Animals: Fifty‐five dogs; 58 THAs. Methods: Eighty cobalt‐chromium BFX THAs were reviewed, 58 met inclusion criteria. Implant size, positioning, and major complications within 12 months of surgery were recorded. Femoral canal flare (FCF), canal fill, stem angle, and subsidence at 3 months were measured from postoperative radiographs. Appropriateness of final stem size was assessed with digital templates. Odds ratios for associations were calculated. Results: Mean ± SD coronal canal fill (Fillcor ) was 75% ± 6, FCF was 2.0 ± 0.3, and subsidence was 1.7 mm ± 2.6. Stem angulation ranged from 7° varus to 6° valgus, and 7° cranial to 3° caudal. Appropriately sized stems (n = 45) had a mean Fillcor of 78%. Major stem complications occurred in 12% of THAs. Femora with subsidence > 3 mm were 45.3 times more likely to develop postoperative stem complications ( P = .02). Stems with varus angulation ≥ 5° were 12.5 times more likely to sustain intraoperative fissures ( P = .03). Stems considered undersized based on postoperative digital templating were 5.6 times more likely to develop stem complications ( P = .04) and 5.7 times more likely to subside > 3 mm ( P = .03). Conclusion: Varus stem angulation should be avoided to prevent fissures. Canal fill is a poor indicator of optimal stem size and the current recommendation of >85% is unnecessarily high. Postoperative templating may be useful for assessing appropriateness of stem size.